INFLUENCE OF SERVICE QUALITY AND PRICE AND LOCATION ON CUSTOMER SATISFACTION AT RESTAURANT SERVICE AT EMERALD GARDEN HOTEL MEDAN - Elisabet Br Mungkur; Nurhayati Nurhayati (SEAN Institute, 2023)
In the current era of industry 4.0, the business world is running very rapidly, including businesses in the food sector. Quality of service is a great way to attract more new customers, retain existing customers, keep customers away, and create new and special innovations. In addition to service quality, another factor is price which affects customer satisfaction. Price is a major factor in doing business. Many businesses go out of business due to unreactive prices, assuming that customers who come to the Emerald Garden Hotel Medan have varying desires or stimuli in maintaining the service products provided, whether booking lodging, utilizing existing facilities such as meeting facilities, entertainment and others. ”. Hotel Grand Emerald GARDEN Medan has 152 rooms with an average occupancy rate of 83% every day so that the population taken in this study is the personal guests of the Emerald garden hotel in April. The population taken in this study are all 450 guests who eat restaurant at the Emerald Garden Hotel Medan. taken were completed to 113 respondents, with random sampling technique. The results of hypothesis testing show that partially the service quality variable has a t-count value of 0.092 and a t-table value of 1.982. This means that the value of t count <t table (0.092 <1.982) and the significance value is greater than the significance level (0.927> 0.05). This means that service quality does not have a close relationship with customer satisfaction, if service quality increases or decreases, then will not affect consumer satisfaction. So, the result of this test is that service quality has no effect on customer satisfaction. So that H1 is rejected and Ho is accepted.